1991
DOI: 10.1029/91jb02030
|View full text |Cite
|
Sign up to set email alerts
|

Surficial offsets on the Central and Eastern Garlock Fault associated with prehistoric earthquakes

Abstract: Geomorphic features offset along the central and eastern Garlock fault record the amount of surface slip associated with prehistoric earthquakes. Along the easternmost 90 km of the fault, the smallest offsets cluster around 2–3 m of left‐lateral slip, apparently associated with the most recent earthquake on this portion of the fault. Larger offsets along this part of the fault, especially in Pilot Knob Valley, cluster around values consistent with 2–4 m of slip in each of the past several events. Farther west,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 35 publications
(5 reference statements)
3
146
1
Order By: Relevance
“…One simple observation may help to guide the interpretation of some offset geomorphic features: in cases where there are multiple downstream channel or gully segments offset from a single source, the channel segments offset a larger amount must have been offset in more than one earthquake. Although this configuration is somewhat rare, it has been found along several strike-slip faults [Sieh, 1978;McGill and Sieh, 1991 Figure 10a has been offset in more than one earthquake. This is not a trivial observation, since one could argue that the Garlock fault is long enough to produce an earthquake with 8.8 m of displacement [Wells' and Coppersmith, 1994].…”
Section: Other Approachesmentioning
confidence: 99%
“…One simple observation may help to guide the interpretation of some offset geomorphic features: in cases where there are multiple downstream channel or gully segments offset from a single source, the channel segments offset a larger amount must have been offset in more than one earthquake. Although this configuration is somewhat rare, it has been found along several strike-slip faults [Sieh, 1978;McGill and Sieh, 1991 Figure 10a has been offset in more than one earthquake. This is not a trivial observation, since one could argue that the Garlock fault is long enough to produce an earthquake with 8.8 m of displacement [Wells' and Coppersmith, 1994].…”
Section: Other Approachesmentioning
confidence: 99%
“…Some workers have concluded that measurements of a factor of 20%-100% in slip variability over distances of tens to hundreds of meters are not uncommon, after studying the lateral variability of slip based on offset geomorphic features after the Landers earthquake (McGill and Rubin, 1999). This has implications for discriminating between one or multiple discrete events or estimating the size of past earthquakes (Sieh, 1978;Rockwell and Pinault, 1986;Lindvall et al, 1989;McGill and Sieh, 1991;Weldon et al, 1996;McGill and Rubin, 1999) using displaced deposits in trenches or offset geomorphic features. After the M 7.4 İzmit earthquake of 17 August 1999 and the M 7.1 Düzce earthquake of 12 November 1999, teams of geologists mapped the surface ruptures and measured hundreds of offset geomorphic and cultural features in order to resolve slip distribution (Figs.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that there may be considerable strain accumulated that could be released in large earthquakes. Rupture of short segments of the Garlock Fault could produce M w 6.6 to 7.5 earthquakes (McGill and Sieh, 1991). The largest potential earthquake (M w ~7.8) could result from the (unlikely) rupture of the entire length of the fault.…”
Section: Seismic Hazardsmentioning
confidence: 99%